EU GDPR & EU-U.S. privacy shield : a pocket guide - Calder, Alan, 1957- (IT Governance Publishing, 2019)
This concise guide is essential reading for US organizations wanting an easy to follow overview of the GDPR and the compliance obligations for handling data of EU citizens, including guidance on the EU-U.S. Privacy Shield.